Case Report: Multiple mesenchymal hamartomas showing spontaneous motility in the nasopharynx - Kinoshita, Tetsuya; Kono, Masamitsu; Iwamoto, Ryuta; Hijiya, Masayoshi; Takeda, Saori; Ohtani, Makiko; Doyama, Mikako; Murakami, Daichi; Tamagawa, Shunji; Murata, Shin-Ichi; Hotomi, Muneki (Frontiers in Oncology, 2025)
Hamartomas are classified as either epithelial, mesenchymal, or epithelium-mesenchymal mixed types. They occur extremely rarely in the nasopharynx. A 58-year-old man had multiple tumors with repeating contraction and relaxation in the nasopharynx shown on endoscopy. One of the tumors was endoscopically resected under general anesthesia for histological examination and was finally diagnosed as mesenchymal hamartoma. Smooth muscle tissue is sometimes confirmed in mesenchymal hamartomas, but spontaneous contraction in nasopharyngeal hamartomas is rare. In this case, coexistence of muscle tissue, Cajal interstitial cell-like cells, and ganglion cells was thought to be a mechanism of spontaneous motility of the tumors. Aberrant or residual foregut tissue in the nasopharynx due to embryological factors may be a contributing factor to the multiple occurrences.